Bioremediation of Heavy Metals in Liquid Media Through Fungi Isolated from Contaminated Sources - Joshi, P. K. (Springer-Verlag, 2011)
Wastewater particularly from electroplating, paint, leather, metal and tanning industries contain enormous amount of heavy metals. Microorganisms including fungi have been reported to exclude heavy metals from wastewater through bioaccumulation and biosorption at low cost and in eco-friendly way. An attempt was, therefore, made to isolate fungi from sites contaminated with heavy metals for higher tolerance and removal of heavy metals from wastewater. Seventy-six fungal isolates tolerant to heavy metals like Pb, Cd, Cr and Ni were isolated from sewage, sludge and industrial effluents containing heavy metals. Four fungi (Phanerochaete chrysosporium, Aspegillus awamori, Aspergillus flavus, Trichoderma viride) also were included in this study. The majority of the fungal isolates were able to tolerate up to 400 ppm concentration of Pb, Cd, Cr and Ni. The most heavy metal tolerant fungi were studied for removal of heavy metals from liquid media at 50 ppm concentration. Results indicated removal of substantial amount of heavy metals by some of the fungi. With respect to Pb, Cd, Cr and Ni, maximum uptake of 59.67, 16.25, 0.55, and 0.55 mg/g was observed by fungi Pb3 (Aspergillus terreus), Trichoderma viride, Cr8 (Trichoderma longibrachiatum), and isolate Ni27 (A. niger) respectively. This indicated the potential of these fungi as biosorbent for removal of heavy metals from wastewater and industrial effluents containing higher concentration of heavy metals.